The M25 gene products are critical for the cytopathic effect of mouse cytomegalovirus. Issue 1 (December 2017) - Kutle, Ivana; Sengstake, Sarah; Templin, Corinna; Glaß, Mandy; Kubsch, Tobias; Keyser, Kirsten; Binz, Anne; Bauerfeind, Rudolf; Sodeik, Beate; Čičin-Šain, Luka; Dezeljin, Martina; Messerle, Martin
Abstract Cell rounding is a hallmark of the cytopathic effect induced by cytomegaloviruses. By screening a panel of deletion mutants of mouse cytomegalovirus (MCMV) a mutant was identified that did not elicit cell rounding and lacked the ability to form typical plaques. Altered cell morphology was assigned to the viral M25 gene. We detected an early 2.8 kb M25 mRNA directing the synthesis of a 105 kDa M25 protein, and confirmed that a late 3.1 kb mRNA encodes a 130 kDa M25 tegument protein. Virions lacking the M25 tegument protein were of smaller size because the tegument layer between capsid and viral envelope was reduced. The ΔM25 mutant did not provoke the rearrangement of the actin cytoskeleton observed after wild-type MCMV infection, and isolated expression of the M25 proteins led to cell size reduction, confirming that they contribute to the morphological changes. Yields of progeny virus and cell-to-cell spread of the ΔM25 mutantin vitro were diminished and replicationin vivo was impaired. The identification of an MCMV gene involved in cell rounding provides the basis for investigating the role of this cytopathic effect in CMV pathogenesis.